Novel Approach in Enhancing Science Education through Problem-Based Creative Learning and Delphi Evaluation - Annur Indra Kusumadani; Affandy, Harry; Sunarno, Widha; Suryana, Risa; Harjana, Harjana; Andiena, Resty Zama (Jurnal Pendidikan IPA Indonesia, 2024)
The research aimed to optimize the Problem-Based Creative Learning (PBCL) model to enhance higher-order thinking skills (HOTS) in natural science learning. The research used the Delphi method, which involved seven experts in education from various disciplines contributing to a cycle of Delphi. The Delphi cycle consisted of two cycles, and data analysis involved using the Aiken V statistical equation. The Delphi study results highlighted agreement on the characteristics of the PBCL model, which included (1) syntax, (2) social system, (3) principles of reaction, (4) support system, and (5) the impact of learning. The research findings highlight the potential of PBCL as an innovative learning model in natural science learning, emphasizing its effectiveness in improving aspects of analysis, evaluation, and creation as part of HOTS. The study contributes a learning model framework for educators to strengthen natural science education and cultivate insightful and adaptive students in the 21st century.